Pendidikan dan Modernitas Barat dalam Sastra Dunia Ketiga - Agus R Sarjono (HISKI, 2005)
Post-Independence, colonialism leaves a complex cultural problem. The old culture that has been slowly deteriorating due to the penetration of Western culture tries hard to stay alive and sometimes can even produce its local genius, on the other hand, that same Western culture can never really settle as an integral part of the Third World. Colonization is not an experience that can be easily forgotten. That is why colonialism remains a prevalent theme in the national literature of a once colonized people. Following conquest and armed violence, the process of disseminating Western modernity is carried out through education, so Western education often becomes a problematic part of the Third World. Some welcome it warmly, some try to fight and resist it, while others are ambivalent, unable to decide whether they should reject or accept it. By using examples of short stories from Thailand, China, and novels by Chinua Achebe, Jose Rizal, F. Sionil Jose, Sutan Takdir Alisyahbana, Armijn Pane, and Okot p;Bitek, the portrayal of Western education in the Third World literature is discussed, as well as its impact on education and social conflict in Indonesia today.Kata kunci: pendidikan, kolonialisasi, modernitas, tradisi